Are we waiting for the sky to fall? Predictors of withdrawal of life-sustaining support in older trauma patients: A retrospective analysis. Issue 3 (29th March 2023) - Badrinathan, Avanti; Ho, Vanessa P.; Tinkoff, Glen; Houck, Olivia; Vazquez, Daniel; Gerrek, Monica; Kessler, Ann; Rushing, Amy
Abstract : Advance directives may be markers of withdrawal of treatment, but other hospital events have a greater impact. Providers must perform more proactive discussions of end-of-life care. Abstract : BACKGROUND: Limited data exist regarding the impact of advanced care planning for injured geriatric patients. We hypothesized that patients with advance directives limiting care (ADLC) compared with those without ADLC are more likely to undergo withdrawal of life-sustaining support (WLSS). METHODS: This is a propensity-matched analysis utilizing American College of Surgeons Trauma Quality Improvement Program patients 65 years or older who presented between 2017 and 2018. Patients with and without ADLC on admission were compared. The primary outcome was WLSS and days prior to WLSS. Additional factors examined included hospital length of stay (LOS), unplanned operations, unplanned intensive care unit admissions, and in-hospital cardiac arrests. Prior to matching, logistic regression model assessed factors associated with WLSS. Patients with and without ADLC were matched 1:1 via a propensity score using patient and injury factors as covariates, and matched pair analysis compared differences in WLSS between patients with and without ADLC. RESULTS: There were 597, 840 patients included: 44, 001 patients with an ADLC (7.36%) compared with 553, 839 with no ADLC (92.64%). Patients with an ADLC underwent WLSS more often than those with no ADLC (7.68% vs. 2.48%, p < 0.001). In a 1:1 propensity-matched analysis, patients with ADLC were more likely to undergo WLSS (odds ratio [OR], 2.38' 95% confidence interval [CI], 2.22–2.55), although stronger predictors of WLSS included severity of injury (Injury Severity Score, 25+; OR, 23.84; 95% CI, 21.55–26.36), unplanned intensive care unit admissions (OR, 3.30; 95% CI, 2.89–3.75), and in-hospital cardiac arrests (OR, 4.97; 95% CI, 4.02–6.15). CONCLUSION: A small proportion of the geriatric trauma population had ADLC on admission. While ADLC was predictive of WLSS, adverse events were more strongly associated with WLSS. To ensure patient-centered care and reduce futile interventions, surgeons should delineate goals of care early regardless of ADLC. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level III. Abstract :